Near-miss injury of multiple Carpometacarpal joint dislocations: a report of two cases - Kow, Ren Yi; Mustapha Zakaria, Zaharul Azri; Kumar, Ruben Jaya; Low, Chooi Leng; Siron @ Baharom, Khairul Nizam (Universiti Malaysia Sabah, 2021)
Multiple carpometacarpal joint (CMCJ) dislocations are rare and are easily missed. The anatomical configuration renders stability to the joints. As a result, a high-velocity impact is required to dislocate the joint. We present two cases of multiple carpometacarpal joint dislocations with different mechanisms of injury and their subsequent management at our centre. In case 1, a 29-year-old gentleman presented with acute dislocations of the CMCJs involving the right middle, ring, and little fingers. An open reduction and fixation with Kirschner wires were done to stabilize the dislocated CMCJs and he subsequently recovered. In case 2, a 25-year-old gentleman had the CMCJ dislocations detected late due to other more profound injuries. Partial arthrodesis was performed to address the instability of the CMCJs of the right index, middle and ring fingers. He subsequently recovered and returned to work 6-months postoperatively. The diagnosis of carpometacarpal joint dislocation can be easily missed especially when there is a concurrent distracting injury. It is crucial to maintain a high index of suspicion as early diagnosis and prompt treatment is paramount to yield a better outcome.